Relation of FTO gene variants to fetal growth trajectories: Findings from the Southampton Women's survey. (February 2016) - Barton, S.J.; Mosquera, M.; Cleal, J.K.; Fuller, A.S.; Crozier, S.R.; Cooper, C.; Inskip, H.M.; Holloway, J.W.; Lewis, R.M.; Godfrey, K.M.
Abstract: Introduction: Placental function is an important determinant of fetal growth, and fetal growth influences obesity risk in childhood and adult life. Here we investigated how FTO and MC4R gene variants linked with obesity relate to patterns of fetal growth and to placental FTO expression. Methods: Southampton Women's Survey children (n = 1990) with measurements of fetal growth from 11 to 34 weeks gestation were genotyped for common gene variants in FTO (rs9939609, rs1421085) and MC4R (rs17782313). Linear mixed-effect models were used to analyse relations of gene variants with fetal growth. Results: Fetuses with the rs9939609 A:A FTO genotype had faster biparietal diameter and head circumference growth velocities between 11 and 34 weeks gestation (by 0.012 (95% CI 0.005 to 0.019) and 0.008 (0.002–0.015) standard deviations per week, respectively) compared to fetuses with the T:T FTO genotype; abdominal circumference growth velocity did not differ between genotypes. FTO genotype was not associated with placental FTO expression, but higher placental FTO expression was independently associated with larger fetal size and higher placental ASCT2, EAAT2 and y + LAT2 amino acid transporter expression. Findings were similar for FTO rs1421085, and the MC4R gene variant was associated with the fetal growth velocity of head circumference. Discussion: FTO gene variants are known to associate with obesity but this is the first time that the risk alleles and placental FTO expression have been linked with fetal growth trajectories. The lack of an association between FTO genotype and placental FTO expression adds to emerging evidence of complex biology underlying the association between FTO genotype and obesity. Highlights: Variants in the FTO gene are previously known to be associated with obesity. discovered novel associations between FTO variants and growth trajectory of fetal head measures. also found novel associations between placental FTO expression and fetal size.